2019
DOI: 10.1002/adfm.201903621
|View full text |Cite
|
Sign up to set email alerts
|

SnO2‐C60 Pyrrolidine Tris‐Acid (CPTA) as the Electron Transport Layer for Highly Efficient and Stable Planar Sn‐Based Perovskite Solar Cells

Abstract: For solar cell applications, Sn-based hybrid perovskites have drawn particular interest due to their environmental friendliness. Here, a thin layer of C 60 pyrrolidine tris-acid (CPTA) is found essential for achieving high efficiency with planar solar cells of Sn-based perovskites. As a result, a power conversion efficiency of 7.40% is achieved for {en}FASnI 3 solar cells with a planar n-i-p architecture, and the device exhibits excellent stability in air. For the first time, highly efficient Sn-based hybrid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…Recently, Diau et al summarized the properties of inverted and normal tin‐based PSCs, and found the inverted structure has high and stable performance, and Sn 2+ /Sn 4+ oxidation is even less obvious in inverted devices. [ 138 ] So, constructing the inverted structure and combining the current new hole transport layer [ 139 ] and electron transport layer [ 140 ] to develop an efficient and stable tin‐based PSCs should be an efficient approach.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Recently, Diau et al summarized the properties of inverted and normal tin‐based PSCs, and found the inverted structure has high and stable performance, and Sn 2+ /Sn 4+ oxidation is even less obvious in inverted devices. [ 138 ] So, constructing the inverted structure and combining the current new hole transport layer [ 139 ] and electron transport layer [ 140 ] to develop an efficient and stable tin‐based PSCs should be an efficient approach.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…[11][12][13][14] The sundry organic and inorganic materials have been used as interface modification for the electron transport layer (ETL) in conventional n-i-p formal architecture to improve the interfacial energy level alignment, reduce the interface trap-state and promote the interface carrier extraction. [15][16][17][18][19][20][21][22][23] The p-i-n inverted architecture devices, especially NiO x -based inverted PSCs, have exhibited many advantages, such as low-temperature solution processing and negligible hysteresis. [24] However, inverted architecture devices are still suffering low PCE because of the large energy offset and undesirable charge carrier extraction at the interface.…”
Section: Doi: 101002/smtd202000478mentioning
confidence: 99%
“…For instance, buffer layer is inserted to reduce the lattice mismatch induced interface stress and induce more ordered crystal growth. [15,16,20,21] In addition, as the principal material in n-i-p-type PSCs, perovskite absorbs light, generates electron/hole carriers and drives carriers to corresponding electrodes. Therefore, the optimization of perovskite materials is equally critical, and the optimization of perovskite active layer can improve the interface defect and crystallinity of perovskite materials at the same time.The perovskite materials used in this study have ABX 3 structures in which A is general organic cation, B is metal ions, and X is halogen examples.…”
mentioning
confidence: 99%